Protective effects of dioscin against Parkinson's disease via regulating bile acid metabolism through remodeling gut microbiome/GLP-1 signaling - Zhang Mao; Haochen Hui; Xuerong Zhao; Lina Xu; Yan Qi; Lianhong Yin; Liping Qu; Lan Han; Jinyong Peng (Elsevier, 2023)
It is necessary to explore potent therapeutic agents via regulating gut microbiota and metabolism to combat Parkinson's disease (PD). Dioscin, a bioactive steroidal saponin, shows various activities. However, its effects and mechanisms against PD are limited. In this study, dioscin dramatically alleviated neuroinflammation and oxidative stress, and restored the disorders of mice induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). 16 S rDNA sequencing assay demonstrated that dioscin reversed MPTP-induced gut dysbiosis to decrease Firmicutes-to-Bacteroidetes ratio and the abundances of Enterococcus, Streptococcus, Bacteroides and Lactobacillus genera, which further inhibited bile salt hydrolase (BSH) activity and blocked bile acid (BA) deconjugation. Fecal microbiome transplantation test showed that the anti-PD effect of dioscin was gut microbiota-dependent. In addition, non-targeted fecal metabolomics assays revealed many differential metabolites in adjusting steroid biosynthesis and primary bile acid biosynthesis. Moreover, targeted bile acid metabolomics assay indicated that dioscin increased the levels of ursodeoxycholic acid, tauroursodeoxycholic acid, taurodeoxycholic acid and β-muricholic acid in feces and serum. In addition, ursodeoxycholic acid administration markedly improved the protective effects of dioscin against PD in mice. Mechanistic test indicated that dioscin significantly up-regulated the levels of takeda G protein-coupled receptor 5 (TGR5), glucagon-like peptide-1 receptor (GLP-1R), GLP-1, superoxide dismutase (SOD), and down-regulated NADPH oxidases 2 (NOX2) and nuclear factor-kappaB (NF-κB) levels. Our data indicated that dioscin ameliorated PD phenotype by restoring gut dysbiosis and regulating bile acid-mediated oxidative stress and neuroinflammation via targeting GLP-1 signal in MPTP-induced PD mice, suggesting that the compound should be considered as a prebiotic agent to treat PD in the future.